P.127: 55 Inches 3D Short‐Throw Rear‐Projection‐System with Broadband Polarizing‐type Glasses. Issue 1 (1st July 2013) - Chen, Sheng‐Hao; Chen, Yi‐Jiun; Lin, Hoang Yan
Abstract: In order to realizing a large‐sized glass‐type 3D display, a 55" screen 3D rear projection system is built. The number and the order of retarders used in the glasses are optimized to reduce the crosstalk and color‐shift caused by head‐rotation. The result shows that image quality is greatly improved.